Contribution of Iraqi women in development: from the perspective faculty members to the complex Jadiriyah/University of Baghdad - افتخار عبد الرزاق عبد الله ايمان رحيم سالم (مجلة كلية التربية للبنات, 2019)
The researchers in this study, which aimed to find out Degree contribution of Iraqi women in development from the perspective faculty members of the complex Jadriya University in Baghdad, and the the impact of demographic variables (gender, college, place of living, school level,) for its contribution. The study population consisted of some faculty members Jadiriyah compound in Baghdad's University for the academic year 20012/2013. This study followed a descriptive approach the field, and the analytical method, the study sample consisted of (250) teaching all of College of Science for girls and education for girls, and to achieve objective of the study was the development of a questionnaire, was sure of its sincerity and the coefficient of stability, was calculated reliability coefficient by Cronbach's alpha equation "was ((81.3%) which meeting the objectives the study. after the process of collecting questionnaires, have been coded and entered into a computer and processed statistically. using the statistical package is SPSS. The study revealed the following results: 1-There were no statistically significant differences at the level of significance (@ = 0.05) of the contribution of Iraqi women in development from the perspective faculty members at the University of Baghdad attributed to the place of living qualification variables. 2-All fields of study got great approval with the exception of domestic the field, as earned had a moderate consent. It was presented a number of recommendations to improve the contribution of Iraqi women in development.